2006
DOI: 10.1152/japplphysiol.00126.2006
|View full text |Cite
|
Sign up to set email alerts
|

Contractile properties of EDL and soleus muscles of myostatin-deficient mice

Abstract: Myostatin is a negative regulator of muscle mass. The impact of myostatin deficiency on the contractile properties of healthy muscles has not been determined. We hypothesized that myostatin deficiency would increase the maximum tetanic force (P(o)), but decrease the specific P(o) (sP(o)) of muscles and increase the susceptibility to contraction-induced injury. The in vitro contractile properties of extensor digitorum longus (EDL) and soleus muscles from wild-type (MSTN(+/+)), heterozygous-null (MSTN(+/-)), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
158
4
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(189 citation statements)
references
References 72 publications
22
158
4
5
Order By: Relevance
“…Here, we showed that Mstn gene deletion results in reduced lipolytic machinery in Mstn deficient hypertrophic muscles (impaired mitochondrial yield, CS and β-HAD activities and Cpt1 and Ppar- gene expressions), in line with previous studies showing that oxidative metabolism is diminished in several models of Mstn deficiency [12,13,15,16,51]. In addition, we demonstrated that the levels of cytosolic (FABP3) and sarcolemmal lipid transporters (FATP1, FATP4) are reduced, in agreement with our previous observation showing a significant reduction of FAT/CD36 levels [16].…”
Section: Myostatin and Muscle Lipid Metabolismsupporting
confidence: 90%
See 1 more Smart Citation
“…Here, we showed that Mstn gene deletion results in reduced lipolytic machinery in Mstn deficient hypertrophic muscles (impaired mitochondrial yield, CS and β-HAD activities and Cpt1 and Ppar- gene expressions), in line with previous studies showing that oxidative metabolism is diminished in several models of Mstn deficiency [12,13,15,16,51]. In addition, we demonstrated that the levels of cytosolic (FABP3) and sarcolemmal lipid transporters (FATP1, FATP4) are reduced, in agreement with our previous observation showing a significant reduction of FAT/CD36 levels [16].…”
Section: Myostatin and Muscle Lipid Metabolismsupporting
confidence: 90%
“…Indeed, beyond muscle hypertrophy, Mstn KO mice show a disturbed muscle function with loss of muscle strength and endurance in vivo or ex vivo accompanied with a decrease in mechanical performance, and ATP production during exercise [11,12,13,14]. In parallel, many other metabolic changes have been documented in Mstn KO muscle such as a decrease in mitochondrial content, disturbance in mitochondrial respiratory function with a decay in the respiratory control ratio in intermyofibrillar mitochondria, and a decline in porine activity [11,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle mass, fiber length, and maximum isometric tetanic force were measured. These measurements were used to determine total crosssectional area and specific force (kN/m 2 ) (53,57). The susceptibility to contraction-induced injury was determined after lengthening contractions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, myostatin-null mice gain mass in both their EDL and SOL; however, functional testing shows that specific contractile force is less than controls for myostatin cKO EDL and the same as controls for cKO SOL (55)(56)(57). Conditional deletion of IGF-1 in muscle was found to be selective for fast twitch EDL where mass and maximum power increased about 30% (58).…”
Section: Discussionmentioning
confidence: 96%